Occipital fibrous nodules leading to late diagnosis of tuberous sclerosis complex. - Jindal, Alok; Singla, Isha; Aditi; Goel, Shitij (European Journal of Pediatric Dermatology, 2025)
Tuberous sclerosis complex (TSC) is a multisystem genetic disorder often first suspected based on cutaneous findings. We report the case of a 16-year-old boy with facial angiofibromas and asymptomatic nodules on the occipital scalp. Cutaneous examination revealed a fibrous plaque on the occipital region, a rare lesion but recognized as a major diagnostic criterion for TSC. Its unusual location prompted further diagnostic evaluation, which confirmed the diagnosis of TSC. This case highlights the importance of a thorough examination of the skin and scalp in children with subtle or resolved neurologic signs. Recognizing atypical presentations of classical lesions, such as occipital fibrous plaques, can facilitate timely diagnosis and guide appropriate systemic screening in TSC.